The Activities of the Gelsolin Homology Domains of Flightless-I in Actin Dynamics - Pintér, Réka; Huber, Tamás; Bukovics, Péter; Gaszler, Péter; Vig, Andrea Teréz; Tóth, Mónika Ágnes; Gazsó-Gerhát, Gabriella; Farkas, Dávid; Migh, Ede; Mihály, József; Bugyi, Beáta (Frontiers in Molecular Biosciences, 2020)
Flightless-I is a unique member of the gelsolin superfamily alloying six gelsolin homology domains and leucine-rich repeats. Flightless-I is an established regulator of the actin cytoskeleton, however, its biochemical activities in actin dynamics are still largely elusive. To better understand the biological functioning of Flightless-I we studied the actin activities of Drosophila Flightless-I by in vitro bulk fluorescence spectroscopy and single filament fluorescence microscopy, as well as in vivo genetic approaches. Flightless-I was found to interact with actin and affects actin dynamics in a calcium-independent fashion in vitro. Our work identifies the first three gelsolin homology domains (1-3) of Flightless-I as the main actin-binding site; neither the other three gelsolin homology domains (4-6) nor the leucine-rich repeats bind actin. Flightless-I inhibits polymerization by high-affinity (~ nM) filament barbed end capping, moderately facilitates nucleation by low-affinity (~ µM) monomer binding, and does not sever actin filaments. Our work reveals that in the presence of profilin Flightless-I is only able to cap actin filament barbed ends but fails to promote actin assembly. In line with the in vitro data, while gelsolin homology domains 4-6 have no effect on in vivo actin polymerization, overexpression of gelsolin homology domains 1-3 prevents the formation of various types of actin cables in the developing Drosophila egg chambers. We also show that the gelsolin homology domains 4-6 of Flightless-I interact with the C-terminus of Drosophila Disheveled-associated activator of morphogenesis formin and negatively regulates its actin assembly activity.